2023
DOI: 10.1080/17461391.2023.2213185
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolomic adaptations following a 12‐week high‐intensity interval training combined to citrulline supplementation in obese older adults

Abstract: Physical activity and nutrition play important roles in preventing adverse health outcomes that accompany aging. It has been shown that high-intensity interval training (HIIT) combined with citrulline (CIT) supplementation can improve physical and functional capacities. The aim of this study was to evaluate serum metabolites following a 12-week HIIT combined or not with CIT in obese older adults, and to correlate the metabolic changes with clinico-biological parameters changes. Eighty-six obese older adults co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 40 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…The majority of the analysed scientific articles demonstrated statistically significant effects of HIIT and DS on BF and induced a reduction of %FAT, body fat mass, BMI, or waist-to-hip ratio [32,33,36,[39][40][41][42][43][44]. On the contrary, two investigations [35,37] did not find any effects of HIIT combined with DS on BF in older adults with overweight and obesity.…”
Section: Effects Of Hiit Combined With Supplementation On Bfmentioning
confidence: 93%
See 4 more Smart Citations
“…The majority of the analysed scientific articles demonstrated statistically significant effects of HIIT and DS on BF and induced a reduction of %FAT, body fat mass, BMI, or waist-to-hip ratio [32,33,36,[39][40][41][42][43][44]. On the contrary, two investigations [35,37] did not find any effects of HIIT combined with DS on BF in older adults with overweight and obesity.…”
Section: Effects Of Hiit Combined With Supplementation On Bfmentioning
confidence: 93%
“…Its serum concentration positively correlates with BF mass, and leptin resistance is another feature of obesity and type 2 diabetes [55]. In the current review, only one study assessed the effects of HIIT + DS on leptin [44]. The authors found that HIIT consisting of 30 min exercise sessions combined with citrulline (an amino acid) significantly reduced serum leptin in older adults with obesity and HIIT+ citrulline-induced effects were more profound compared to HIIT alone [44].…”
Section: Adipokinesmentioning
confidence: 93%
See 3 more Smart Citations